Evolution of IT Project Management Methodologies: Adaptability of Modern Methodologies - Chomiak-Orsa, Iwona; Arutiunian, Violetta (Ewolucja metodyk zarządzania projektami IT: adaptacyjność nowoczesnych metodologii, 2023)
Aim: The purpose of this article is to explore and present modern IT project management methodologies that have emerged over the past decade. The article aims to fill a research gap regarding contemporary, innovative methodologies that go beyond widely used and well-studied approaches such as Scrum and Kanban. By analysing new trends and approaches, the article seeks to provide up-to-date information and tools for IT project managers looking to stay current with the latest industry practices. Methodology: The article employs a comparative analysis of traditional and modern IT project management methodologies, examining their fundamental principles, unique features, and adaptability across various organizational contexts. The methodology includes an analysis of reports such as the State of Agile to highlight practical applications and challenges faced by practitioners. Results: The findings indicate the growing popularity of modern methodologies, emphasizing their benefits, such as flexibility, collaboration, and alignment with business needs. The analysis also discusses implementation barriers, such as resistance to change and lack of leadership support, as well as emerging trends like hybrid work models. Implications and recommendations: Organizations are encouraged to foster a culture of openness to change, provide training on modern methodologies, and leverage support from the Agile community. The importance of leadership engagement and adapting methodologies to hybrid work models is highlighted to enhance project outcomes. Originality/value: This work provides a comprehensive overview of modern IT project management methodologies, bridging theory and practice. Its originality lies in linking global changes, such as hybrid work trends, with practical challenges in adapting methodologies.
Business Informatics = Informatyka Ekonomiczna, 2023, Nr 1-2 (65-66), s. 1-10
Keywords: modern IT project management methodologies; IT project management; innovation in project management; contemporary project management methodologies; development of Agile methodologies; nowoczesne metodyki zarządzania projektami informatycznymi; zarządzanie projektami informatycznymi; innowacje w zarządzaniu projektami; współczesne metodyki zarządzania projektami; rozwój metodyk Agile